(untitled) (The GIST, 2024)
This paper describes the themes and rhemes of Charles Perrault’s short story "Cinderella" as a systematic approach to Systemic functional linguistics. The purpose of this study was to identify the theme and context, classify the types and components of the theme, and describe the relationship between the theme and textual development. The method used in this study is a qualitative method. The data is taken from the short story Cinderella by Charles Perrault. The data were analysed using several theories based on functional English grammar. As a result of this study, we found three types of themes (topical, textual and interpersonal).